ENTREPRENEURIAL LEADERSHIP: A THEORETICAL RESEARCH - Esmer, Yusuf; Dayi, Faruk (International Institute of Social and Economic Sciences, 2016)
In today?s business world, having just leadership qualities by business managers is not enough in order to maintain growth, development and sustainability of enterprises. In addition to this, business managers should be able to seek innovations, opportunities around them and take some risks. Managers with these qualities have both leadership and entrepreneurship characteristics. At this point, the concept of entrepreneurial leadership emerges. Entrepreneurial leadership can be defined as a leader, who is also have the skills of entrepreneurship. In other words, entrepreneurial leadership refers to the managers who can take risks, seize opportunities, pursue innovation and be innovative, producing, interchanging and strategic. In addition, entrepreneurial leadership is creating new products, new processes and expansion opportunities in existing businesses, working in social institutions and dealing with ignored social issues, participating in social and political movements, contributing to the change of current services and policies implemented by civil society organizations and governments. Entrepreneurial leaders know themselves and their environment very well and find new opportunities creating value for businesses, stakeholders and society. The main motivation of leaders is their desire to create social, environmental and economic opportunities. Today, the need for entrepreneurial leaders in businesses is increasing every passing day and the subject of entrepreneurial leadership should investigated by researchers. In this regard, in this study, the concepts of leadership and entrepreneurship are briefly defined in accordance with the earlier studies conducted in this field and the concept of entrepreneurial leadership, which has become increasingly important in the business world, is discussed and the characteristics and dimensions of entrepreneurial leadership and its importance for businesses is emphasized.
Keywords: 9. Industry and infrastructure; 8. Economic growth; 16. Peace & justice; 12. Responsible consumption